Should I Install LaTeX , MiKTeX or TexStudio? - Christian, Ibiloye, Abiodun (My University, 2024)
In various guises, this is a common question, innocent, but actually betraying a fundamental confusion about TeX evolution, directory, and the levels of operation in the TeX/LaTeX family and friends. TeX is a macro typesetting language developed by Donald E. Knuth, and today’s worldwide de facto standard for high-quality digital document typesetting for writers/authors in the academics and publishers of journals and books, including Elsevier, PlosOne, JSON and Nature Springer. LateX and ConTeXt are the two main evolution and revolutionary development 'on top of TeX'. LaTeX is an extension of TeX typesetting macro created by Leslie Lamport, with addition of standard packages and features for plain-tex contents using markup language syntax. It is a free document typesetting and processing system for creating high quality rich document format. That is, outputs in device transferable formats (DVI, PDF, HTML, etc) suitable for websites and submission to journals, academic institutions and publishers for ultimate publication. It is in principle and editing style different from a Word Processor, to encourage and enable authors concentrate more on writing rich contents, leaving document design to expert document designers. MiKTeX is a modern TeX distribution for Microsoft Windows, Linux and macOS, while TexStudio (likewise TeXnicenter) are GUI TeX document editors. This article clears the confusion and give a comprehensive introduction to anyone, (authors including academics) to choose between TeX/LaTeX distributions and editors to install given offered particular feature advantages, the particular of the users' academic field and level of productivity on their project, report or document. **** *SIGNIFICANCE: The author relied on primary source documents, chats with LaTeX development members on stackexchange.com, literatures, and extensive software features testing and hoped this publication fills the gaps in knowledge and literature, aside many plagiarized blogs, confusing articles (as learning LaTeX itself). It details the important breakthroughs in TeX development projects which include the creation of pdfTeX in 2014, graphic editors, GUI and online TeX editors, running external program codes (R, Python, Mathlab, etc) in LaTeX native environment, expl3 language as part of LaTeX kernel in 2020, also syncing/integrating tools to other platforms/environment.
Keywords: Document Typesetting; Guide; LaTeX; Literate Programing; MikTeX; TexStudio